2016
DOI: 10.1080/13607863.2015.1128882
|View full text |Cite
|
Sign up to set email alerts
|

Illness representations in caregivers of people with dementia

Abstract: Objectives: Illness representations shape responses to illness experienced by the self or by others. The illness representations held by family members of those with long-term conditions such as dementia influence their understanding of what is happening to the person and how they respond and provide support. The aim of this study is to explore components of illness representations (label, cause, control and timeline) in caregivers of people with dementia. Method: This was an exploratory study; the data report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 48 publications
0
21
0
Order By: Relevance
“…There is an added complexity from an individual's interpretation of events. Illness representations influence a person's understanding of what is happening . Relatives are less likely than staff to be trained and understand dementia, so evaluation may be mainly about the person in the past and what has been lost.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is an added complexity from an individual's interpretation of events. Illness representations influence a person's understanding of what is happening . Relatives are less likely than staff to be trained and understand dementia, so evaluation may be mainly about the person in the past and what has been lost.…”
Section: Discussionmentioning
confidence: 99%
“…Illness representations influence a person's understanding of what is happening. 47 Relatives are less likely than staff to be trained and understand dementia, so evaluation may be mainly about the person in the past and what has been lost. Staff may also lack understanding of a person's experience but may conceptualize quality of life as quality of care, which could lead to more positive evaluations.…”
Section: Different Understanding and Insightmentioning
confidence: 99%
“…However, these studies did not use the CSM as a conceptual framework and only a few studies have done so. Both Glidewell, Johnston, and Thomas (2012) and Quinn, Jones, and Clare (2017) have qualitatively explored elements of IRs in caregivers of people with dementia. Glidewell (2012) reported a single case study with the person with dementia, the caregiver and the general practitioner, reporting differences in beliefs.…”
mentioning
confidence: 99%
“…Glidewell (2012) reported a single case study with the person with dementia, the caregiver and the general practitioner, reporting differences in beliefs. The caregivers in Quinn et al (2017) attributed the observed changes primarily to changes in the brain. Some felt there were things that people with dementia could do to help manage the condition and others thought nothing could be done.…”
mentioning
confidence: 99%
“…Focusing specifically on the CSM illness perception dimension of causality, patients with mild cognitive impairment and their caregivers most frequently attributed cognitive symptoms to uncontrollable factors like normal aging (Rodakowski, Schulz, Gentry, Garand, & Lingler, 2014). Caregivers of persons with dementia participating in the Memory Impairment and Dementia Awareness Study (MIDAS) responded to semistructured interviews to describe illness representations; caregivers described uncertainty about the cause, timeline, and controllability of patients’ dementia (Quinn, Jones, & Clare, 2016). However, to our knowledge, no studies have comprehensively explored caregivers’ perceptions of their family members’ memory loss.…”
mentioning
confidence: 99%